2011
DOI: 10.1007/s00429-010-0298-1
|View full text |Cite
|
Sign up to set email alerts
|

Different brain structures related to self- and external-agency attribution: a brief review and meta-analysis

Abstract: Several neuroimaging studies have consistently shown activations of areas surrounding the temporo-parietal junction (TPJ) during tasks exploring the sense of agency. Beyond TPJ, activations in different structures, such as the dorsolateral prefrontal cortex (dLPFC), the pre-supplementary motor area (pre-SMA), the insula and the precuneus have been reported. Moreover, a possible dissociation between self- and external-agency attribution has been suggested. To test the hypothesis of distinct neural correlates fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
188
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(213 citation statements)
references
References 64 publications
19
188
0
6
Order By: Relevance
“…The anterior insula has been implicated in temporal processing (Craig, 2009a;Wiener et al, 2010), which has been suggested to relate to its role in integrating internal interoceptive temporal cues with external signals (Wittmann, 2009;Wittmann et al, 2010). Indeed, the anterior insula has been activated in studies investigating temporal synchrony (Bushara et al, 2001) and the sense of agency and error monitoring that require matching exteroceptive sensory signals with self-generated actions (Menon et al, 2001;Klein et al, 2007;Karnath and Baier, 2010;Sperduti et al, 2011;Klein et al, 2013). Therefore, it is possible that the observed increased anterior insular activation by asynchronous cardio-visual stimuli reflects sensitivity to the temporal disparity between the visual stimulus and the cardiac frequency regardless of predictive mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The anterior insula has been implicated in temporal processing (Craig, 2009a;Wiener et al, 2010), which has been suggested to relate to its role in integrating internal interoceptive temporal cues with external signals (Wittmann, 2009;Wittmann et al, 2010). Indeed, the anterior insula has been activated in studies investigating temporal synchrony (Bushara et al, 2001) and the sense of agency and error monitoring that require matching exteroceptive sensory signals with self-generated actions (Menon et al, 2001;Klein et al, 2007;Karnath and Baier, 2010;Sperduti et al, 2011;Klein et al, 2013). Therefore, it is possible that the observed increased anterior insular activation by asynchronous cardio-visual stimuli reflects sensitivity to the temporal disparity between the visual stimulus and the cardiac frequency regardless of predictive mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis, the homologous area in the right hemisphere has been associated with the disruption of the sense of self-agency and an external attribution of the action effect. 57 In conjunction, this region could potentially be involved in the hyperregulation of affect and agency as suggested by recent models of trauma-related dissociation. 7 The detected increase in grey matter volume in the right postcentral and superior temporal gyri is particularly interesting, as this part of the primary somatosensory cortex (Brodmann area [BA] 3) receives thalamocortical projections from the sensory input fields and is involved in the processing of proprioception and body ownership.…”
Section: Increases In Grey Matter Volume In Patients With Dpdmentioning
confidence: 94%
“…Specifically, we hypothesized that metacognitive abilities would reflect differences in gray matter volume (GMV) in prefrontal cortical areas such as BA10, as previously shown in perceptive tasks (Fleming et al, 2010;Miele, Wager, Mitchell, & Metcalfe, 2011), but also in other areas such as the anterior insula and parietal reach regions (PRR), given previous accounts suggesting a key role of these areas in the sense of agency (Farrer et al, 2003(Farrer et al, , 2004Karnath & Baier, 2010a;Karnath, Baier, & Nagele, 2005;Sperduti, Delaveau, Fossati, & Nadel, 2011) and motor awareness (Assal, Schwartz, & Vuilleumier, 2007;Desmurget & Sirigu, 2009;Sirigu et al, 2004). Indeed, the sense of agency is thought to be intimately linked to self-monitoring processes (Frith, Rees, & Friston, 1998) and considered as an implicit form of metacognition (see for a detailed discussion Chambon, Filevich, and Haggard (2014)), because both subjective agency and metacognition share mechanistic features associated with the ability to evaluate the success or quality of one's own task performance.…”
Section: Introductionmentioning
confidence: 99%